PERUBAHAN KADAR TSS ( Total Suspended Solid) DAN PHOSPHATE AIR LIMBAH LAUNDRY DENGAN METODE KOAGULASI DAN FLOKULASI - Nur hayati; Ri yanah (JURNAL TECHLINK, 2018)
Community life is growing along with increasing population and technological advancements. One of them is the use of laundry services that increases directly proportional to the waste produced. Laundry waste containing phosphate derived from Sodium Trypoliphosphate and high TSS (Total Disolved Solid) levels can cause eutrophication and turbidity in water bodies. The purpose of this study was to examine the effect of lime and alum addition in reducing phosphate and TSS (Total Suspended Solid) levels. The research method used is the experimental method, covering the principles of chemical and physical precipitation through the addition of 0.01 lime coagulant; 0.015; 0.02; 0.025 and 0.03 g and alum 0.1; 0.5; and 1.0 g. From the experiments, the best dose of lime and alum was obtained in reducing phosphate and TSS (Total Disolved Solid) levels in laundry wastes in lime weight 0.025 g and 1,000 g alum with a 99.80% removal percentage. Whereas for TSS (Total Disolved Solid) levels with a removal percentage of 90.89%. The processing of laundry waste using the ANOVA test showed an effect of the addition of variations in lime weight and alum to the decrease in phosphate and TSS levels in laundry waste. The results of the Tukey method showed that phosphate and TSS levels from each weight variation had different averages.